2011
DOI: 10.1002/gps.2785
|View full text |Cite
|
Sign up to set email alerts
|

Anxious symptoms and cognitive function in non‐demented older adults: an inverse relationship

Abstract: Objective The goals of this study were to determine the relationship between anxious symptoms and cognitive functioning in a non-demented, community-dwelling elderly sample (N = 48), and to determine the effect of depressive symptoms upon this relationship. Methods Anxious and depressive symptoms were assessed using Symptom Checklist 90-Revised. Cognitive functioning was assessed with the Repeatable Battery for the Assessment of Neuropsychological Status. Results Results indicated that while both cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
4
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 29 publications
2
25
4
2
Order By: Relevance
“…Since moderate anxiety is associated with better performance on some cognitive measures, it appears that anxiety counteracted the negative impact of depressive symptoms on executive functioning. This is contrary to previous investigations of mixed depression and anxiety, which have shown that comorbid depression and anxiety are associated with worse outcomes, including cognitive deficits, compared to either condition alone [37, 49, 52]. This discrepancy may be due to our examination of subthreshold depression and anxiety, rather than clinical conditions.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…Since moderate anxiety is associated with better performance on some cognitive measures, it appears that anxiety counteracted the negative impact of depressive symptoms on executive functioning. This is contrary to previous investigations of mixed depression and anxiety, which have shown that comorbid depression and anxiety are associated with worse outcomes, including cognitive deficits, compared to either condition alone [37, 49, 52]. This discrepancy may be due to our examination of subthreshold depression and anxiety, rather than clinical conditions.…”
Section: Discussioncontrasting
confidence: 91%
“…Investigations comparing patients diagnosed with anxiety disorders, such as obsessive-compulsive disorder, generalized anxiety disorder, and post-traumatic stress disorder typically find anxiety-related attentional biases, executive dysfunction, and memory deficits [34, 35]. In contrast, although some studies have reported a linear relationship between subthreshold anxiety and cognition in older adults [32, 36, 37], many studies in young and older adults show an inverted U-shaped function, such that an intermediate level of anxiety symptoms is associated with optimal cognitive performance, while low and high severity are related to worse functioning [16, 38, 39]. Neuroimaging studies of clinical and subthreshold anxiety suggest that increased anxiety is associated with decreased volumes in the hippocampus and other temporal regions [40, 41], heightened amygdala and insular activity and reduced prefrontal and temporal activity [4247].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has found that anxiety symptoms were significantly and directly associated with depressive symptoms. In one study, taken together, symptoms of anxiety and depression were associated with a decline in cognitive function but the association did not hold for depressive symptoms alone (Stillman, Rowe, Arndt, & Moser, 2012). Therefore, studies that consider only depression or anxiety may be missing participants with milder symptoms of one mood problem that interact with symptoms of the other.…”
Section: Discussionmentioning
confidence: 99%
“…Το εύρηµα αυτό συµφωνεί, σε γενικότερο επίπεδο, τόσο µε ευρήµατα για τη σχέση ακόµη και ήπιου άγχους µε τη γνωστική επίδοση σε υγιείς ηλικιωµένους (Stillman et al, 2012), όσο και µε ευρήµατα για τη σχέση άγχους εξέτασης και ακαδηµαϊκής επίδοσης µαθητών και φοιτητών (Chapell et al, 2005. Lowe et al, 2008.…”
Section: η επίδραση του άγχους εξέτασης στη δοκιµασία σύντοµης γνωστιunclassified